Understanding of Accounting and Training for the Development of MSME’s Financial Statements Based on Sak Emkm - Bokol, Darto Dengi; Ratnawati, .; Perdana, Sukma (International Journal of Small and Medium Enterprises, 2020)
The purpose of this study was to determine the Effect of Accounting Understanding on MSME Financial Reporting Based on SAK EMKM, Effect of Training on Financial Report Preparation on MSME Financial Reporting Based on SAK EMKM. Study at Sanan Tempe Chips Industry Center in Blimbing District, Malang City. The sample of this research is 65 MSME centers of Sanan Tempe Chips Industry in Malang City Blimbing District. Hypothesis testing uses a regression test that is preceded by a normality test, a multicollinearity test, and a heteroscedasticity test. Furthermore, hypothesis testing is done by using multiple regression tests. The results of the study indicate that accounting understanding has no significant effect on MSME financial reporting based on SAK EMKM. Training on the preparation of financial statements has no significant effect on MSME financial reporting based on SAK EMKM.